ANALISIS YURIDIS TERHADAP PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA DENGAN MUTILASI YANG DILAKUKAN OLEH TNI (STUDI KASUS PM PALEMBANG NOMOR. 78-K/ PM.I-04/AD/VII/2019) - Novita Sari Ayu Simanjuntak; Jeklyn Yenni Susi Purba; Rahmat Hidayat Sidabutar; Herman Brahmana (The Juris, 2021)
Crimes againts life in the form of assault on the lives of others, premeditated murder are regulated in article 340 of the Penal Code. In this case also accompanied by mutilation carried out by one member of the Indonesian state army against his lover, mutilation has the sense is the separate limbs of one of the other limbs because of the unnatural perpetrators of self-mutilation of normal people who commit murders accompanied by the act of dis between the victim’s body with his consciousness and emotional background. This study aims (1) to analyze the causative factors of perpetratos committing premeditated murders crimes with mutilation carried out by the TNI (2) analyzing legal sanctions against perpetratos of premeditated murder crimes committed by the TNI (3) analyzing law enforcement in handling cases number 78-K/PM I-04/AD/VII/2019. This legal research is normative legal research of secondary data type which includes primary, secondary, tertiary laws as well as in data collection techniques in research through literature studies.